Angiosperms in Narsingdi district of Bangladesh: Class Magnoliopsida (Bangladesh Journal of Plant Taxonomy, 2020)
This study presents taxonomic information on 468 plant species belonging to 326 genera and 85 families of the angiospermic class Magnoliopsida (dicotyledones) from Narsingdi district of Bangladesh. In this area, Fabaceae with 53 species of 37 genera is the largest family, followed by Asteraceae with 25 species of 24 genera and Rubiaceae with 21 species of 17 genera. Ficus with eight species is appeared as the largest genus, which is followed by Persicaria and Solanum with seven species each, Lindernia with six species, Phyllanthus with five species, and Acacia, Amaranthus, Senna, Sida and Trichosanthes with four species each. Herbs are comprised of 230 (49.14%) species that are followed by trees of 120 (25.64%) species, and shrubs of 118 (25.21%) species. The similarity measured by Jaccard coefficient shows that the six upazilas of Narsingdi district are relatively more similar (75.47%) in their species composition if they are compared all together. However, the similarities vary from 9.03% to 50% if only two upazilas are compared. In this district, total 333 species have been distinguished as economically useful. The species Rauvolfia serpentina of Apocynaceae, Geophila repens of Rubiaceae and Acmella radicans of Asteraceae have been assessed as Endangered (E) in this district.Bangladesh J. Plant Taxon. 27(1): 153-171, 2020 (June)